U-DICTIONARY FOR TEACHING EIGHTH-GRADE STUDENTS’ ENGLISH VOCABULARY MASTERY: IS IT EFFECTIVE? - Aulia, Rizka; Hamidiyah, Aisyah; Baihaqi, Akhmad (Cakrawala Pedagogik, 2024)
This study aimed to determine whether the U-dictionary application is effective in teaching eighth-grade students at MTsN 3 Kota Cilegon to master English vocabulary. This research used a quantitative with quasi-experimental design. This research was conducted at MTsN 3 Kota Cilegon at the academic year 2023-2024. This research used cluster sampling with a sample of 64 students, which consisted of 32 students from the experimental class and 32 students from the control class. In collecting the data, the researcher used a test in the form of a pre-test and post-test of vocabulary mastery to measure the students’ English vocabulary. The data was analyzed with the statistical calculation of the t-test formula through the SPSS version 23 program. The result of this research showed the sig. value (2-tailed) is 0.000, where this value is lower than the significant level of 0.05 (0.000 < 0.05). It is shown that Ha was accepted while H0 was rejected. The effect size obtained is 0.93092, which is included in the large effect category. Therefore, it could be concluded that there is an effect of the U-Dictionary as a learning medium on students' English vocabulary.